Evaluation of hypotesticular activities of different solvent fractions of hydro-methanolic extract of the fruit of Terminalia chebula in Wistar strain adult albino rat: Genomic and flow cytometric approaches - Ghosh, Prabal; Gupta, Priety; Tripathy, Adrija; Das, Barnali; Ghosh, Debidas (Journal of Applied Biomedicine, 2018)
Fruit of Terminalia chebula Retz. (Combretaceae) has male contraceptive folk medicine reputation but its molecular aspect regarding hypotesticular activity is still in dark. The study focused the hypotesticular efficacy of the most potent fraction out of n-hexane, chloroform and ethyl acetate fractions of hydro-methanolic (3:2) extract of Terminalia chebula in connection with male herbal contraceptive development. Treatment with above fractions of Terminalia chebula showed a significant diminution in the activities of androgenic key enzymes (Δ5, 3β-HSD, 17β-HSD) and inhibition in serum testosterone level in compare to the control. Significant up regulation of testicular Bax gene and down regulation of Bcl-2 gene indicated the hypotesticular activity of these fractions. Flow-cytometric study focused a significant diminution in sperm viability and sperm mitochondrial status after the treatment with different fractions. Out of these, ethyl acetate fraction showed most promising hypotesticular effect without impairing any toxicity in general which highlighted that the fraction may contains antitesticular agent(s) in threshold levels compare to other fractions as it decreases spermiological, testicular genomic sensors and elevates sperm apoptotic sensors that may lead to male contraception.
Keywords: Terminalia; testis; látky blokující spermatogenezi; zvířata; Spermatozoa; modely u zvířat; Spermatogenesis-Blocking Agents; mužské pohlaví; Flow Cytometry; Rats, Wistar; průtoková cytometrie; Testis; potkani Wistar; Models, Animal; Animals; rostlinné extrakty; Plant Extracts; spermie; Male